Eritrea : Collective Responsibility for War Orphans - Wolff, Peter H. (World Bank, Washington, DC, 2012)
The note reviews the impact on collective responsibility for orphans in Eritrea, as a result of the thirty-year war, when the number of children who lost both parents increased in geometric proportions. At the same time, the social structure of the traditional society was grossly disrupted, and, as a result, the "grass-roots" pattern of caring for orphans, no longer functioned, and the Eritrean administration had to make special provisions of group care as long as the war lasted. The negative experiences Eritrea had had with foreign adoptions, or foster care, was conducive to concerted efforts to close all orphanages, and instead, formulated a nation-wide plan for the rescue, and rehabilitation of unaccompanied children, largely built on indigenous practices of child care. The plan's main component was the reunification of orphans with their extended family, and an income-generating scheme was implemented, whereby families accepting orphans, received financial assistance - in kind. The program has been in place for some seven years, and is being monitored to provide economic, and social assistance. However, all extended families were not possibly traced, and an alternative plan, provided decent housing, and social environment for children to live together, with one or two surrogate mothers, also based on indigenous traditions of child care among the larger community.